The Effect of the Use of Semicircular Device to Learn the Performance of the Two Stages of Planting in the Box and Raise the Jump Pole for Female Students - Mohammed Naji Shaker Abugneam (Journal of Global Pharma Technology, 2019)
The study included the design, manufacture and use of a semi-circular circular mechanical device. Mechanisms were used to learn the technical stages of performance by jumping the pole for female students. It was installed on the ground. And thus helped the students to perform easily as the effectiveness of bowel jump needs physical and motor abilities in addition to the correct technical performance as well as the general neuromuscular consensus according to the paths of movement, especially for students .The exercise was applied to the device from the group of experimentation Of term (6 weeks) by two units learning at a rate of 12 educational units then it was compared with the control group in reserving the technical performance of the digital level as statistical results showed experimental superiority over the control.Keywords: Design, Educational device, Jumping and learning.